A mensuração da qualidade dos cursos de educação executiva e a avaliação docente : um estudo de caso do IDE - Gritzbach, Flávia Fernandes Brites (2019)
The objective of this study was to analyze whether the teacher evaluation, carried out by the student, can influence the quality of the lato sensu Postgraduate courses. Four individual interviews were conducted in which the systematics of teacher evaluations applied in the courses offered by FGV Management in the city of São Paulo were investigated. The courses studied correspond to more than 6,000 (six thousand) students, involving more than 500 (five hundred) teachers. The main components that could be included in an evaluation system focused on the quality of the course were identified. Finally, a new evaluation system was proposed, involving not only the reformulation of the current evaluation instrument, but also a new way of evaluating, with different instruments, at different times of the course.